2007
DOI: 10.1111/j.1365-2958.2007.05722.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane transport of peptidoglycan precursors across model and bacterial membranes

Abstract: SummaryTranslocation of the peptidoglycan precursor Lipid II across the cytoplasmic membrane is a key step in bacterial cell wall synthesis, but hardly understood. Using NBD-labelled Lipid II, we showed by fluorescence and TLC assays that Lipid II transport does not occur spontaneously and is not induced by the presence of single spanning helical transmembrane peptides that facilitate transbilayer movement of membrane phospholipids. MurG catalysed synthesis of Lipid II from Lipid I in lipid vesicles also did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 33 publications
2
60
0
2
Order By: Relevance
“…MurG was found to catalyze the synthesis of Lipid II from its precursor Lipid I in model membranes, but the resulting Lipid II remained on the synthesis side of the bilayer, excluding the possibility that MurG itself is solely responsible for rapid translocation [21]. Consistent with this finding was the observation that Lipid II synthesis in the bacterial system is not obligatorily coupled to translocation, but must be mediated by a specialized protein machinery [21].…”
Section: Why Polyprenols As Lipid Anchors For the Peptidoglycan Units?supporting
confidence: 70%
See 2 more Smart Citations
“…MurG was found to catalyze the synthesis of Lipid II from its precursor Lipid I in model membranes, but the resulting Lipid II remained on the synthesis side of the bilayer, excluding the possibility that MurG itself is solely responsible for rapid translocation [21]. Consistent with this finding was the observation that Lipid II synthesis in the bacterial system is not obligatorily coupled to translocation, but must be mediated by a specialized protein machinery [21].…”
Section: Why Polyprenols As Lipid Anchors For the Peptidoglycan Units?supporting
confidence: 70%
“…Consistent with this finding was the observation that Lipid II synthesis in the bacterial system is not obligatorily coupled to translocation, but must be mediated by a specialized protein machinery [21]. Transport was found to be ATP or pmf independent and appeared to be coupled to transglycosylation activities on the periplasmic side of the inner membrane [21].…”
Section: Why Polyprenols As Lipid Anchors For the Peptidoglycan Units?supporting
confidence: 66%
See 1 more Smart Citation
“…2) is comprised of the glycopeptide N-acetyl-muramyl-Nacetyl-glucosaminyl-L-Ala-c-D-Glu-L-Lys-D-Ala-D-Ala attached to a C55 hydrophobic tail via a pyrophosphate linker [7]. After synthesis, lipid II is translocated to the periplasmic side of the plasma membrane where the peptidoglycan group is cleaved from the lipid tail and incorporated into the nascent cell wall [8,9]. Vancomycin primarily interacts with the peptidic region of lipid II and the interaction between vancomycin and a range of lipid II peptidoglycan analogs has been studied using a variety of techniques.…”
Section: Introductionmentioning
confidence: 99%
“…At this stage the intact lipid II monomer is translocated across the plasma membrane and is delivered to the periplasmic (exterior) side of the bacterial cell for incorporation into the growing peptidoglycan network. While the mechanism by which this translocation occurs is unknown, recent evidence has shown that it is not a spontaneous process and may be coupled to transglycosylation on the periplasmic cell surface [8].…”
mentioning
confidence: 99%